The fraternal Atlantic: An introduction. Issue 3 (3rd July 2019) - Harland-Jacobs, Jessica L.; Jansen, Jan C.; Mancke, Elizabeth
ABSTRACT: This introduction to the volume on "The Fraternal Atlantic" places the eighteenth-century emergence of freemasonry within the context of the dynamic Atlantic world. It highlights three characteristics that persisted into the twentieth century: the importance of freemasonry to sociability across borders; the tensions within freemasonry between cosmopolitan fraternalism and the turbulent political waters of the modern era, often leading to exclusive practices; and the plasticity of freemasonry that facilitated local adaptations and resiliency. A focus on freemasonry and the fraternal Atlantic offers a bridge between the early modern and modern eras, from the Age of Revolutions to movements for international cooperation after the First World War. It likewise mitigates the tendency of Atlantic scholarship to compartmentalize into various sub-Atlantics, instead seeing the Atlantic world as a zone of interaction with broader global connections.